Application of morbid animal model in drug safety evaluation of traditional Chinese medicine - Ke-Yong, Ning; Min, Li (Frontiers in Pharmacology, 2015)
During thousands of years of clinical validation and practice, the efficacy and safety of traditional Chinese medicine (TCM) have been widely recognized in the prevention and treatment for various diseases. However, further toxicology research of TCM new drugs is still necessary.